Teacher’s Perception on Merdeka Belajar Policy - Prakoso, Bagus Hary; Ramdani, Zulmi; Rahmah, Bilqisthi (Pusat Asesmen dan Pembelajaran, 2020)
The urgency of Merdeka Belajar policy is certainly a challenge for teachers to carry out the learning process in schools. This policy makes teachers have to independently find methods and ways of learning that suit the situation in school. This study aims to explore teachers' perceptions regarding Merdeka Belajar policy that will be applied today. A mixed research design was used in this study by involving thematic content analysis to get an overview of teachers' perceptions about the implementation of Merdeka Belajar policy at schools. Then the researcher tested the extent of the teacher's readiness to use a portfolio instrument which was an implementation of Merdeka Belajar. This study involved 30 teachers who received a set of open-ended questionnaires, conducted the FGD process, and filled out a portfolio assessment questionnaire. The results showed that the majority of teachers considered Merdeka Belajar policy to be an effective alternative in providing instruction to students in accordance with the resources owned by the school. However, technically, teachers feel the need to be given structured socialization, clear guidance, and freedom based on the abilities and personalities of teachers in schools. In addition, the percentage of portfolio instruments usage seems to have been widely practiced in learning activities.